Sinus Lifting in Dentistry and its Importance in Dental Implantation - Hojimuradov Burkhan Ravshanovich (Scientific Trends, 2024)
Incompleteness of the dentition is not only an aesthetic problem, but also quite a medical one, entailing a fairly large number of consequences. To make up for the losses, modern dentistry has a huge arsenal of a wide variety of tools. However, the same dental implants must be installed on a properly prepared jaw, but here there are a number of nuances.